A risk-adapted strategy of adjuvant paclitaxel/carboplatin in early-stage ovarian cancer: Time-dependent effect of 4 versus 6 cycles on outcome - Bamias, A.; Bamia, C.; Karadimou, A.; Soupos, N.; Zagouri, F.; Rodolakis, A.; Haidopoulos, D.; Vlahos, G.; Thomakos, N.; Antsaklis, A.; Dimopoulos, M.A. (Oncology, 2011)
Objective: We investigated the efficacy of risk-adapted adjuvant paclitaxel/carboplatin chemotherapy in early-stage ovarian carcinoma. Methods: Fifty-three patients were treated according to the risk of relapse: patients with stages IA or IB or with grade 1 (low risk) received 4 cycles of paclitaxel and carboplatin; patients with IC/IIA and grade 2 or 3 (high risk) received 6 cycles of chemotherapy. The outcome was compared with that of 95 patients who were all treated with 4 cycles. Results: Median follow-up was 88, 113 and 42 months for the whole cohort, non-risk-adapted and risk-adapted treatment, respectively. Five-year relapse-free and diseasespecific survival was 86 and 93% for the whole population, 96 and 97% for low-risk and 81 and 91% for high-risk patients. Risk classification was the only significant prognostic factor for relapse-free (p = 0.011) and disease-specific survival (p = 0.039). Among high-risk patients, the administration of 6 cycles was associated with a significantly lower relapse rate after censoring events, which occurred beyond 2 years (3 vs. 18%; p = 0.013), but this difference was diminished at 5 years (23 vs. 25%; p = 0.797). Conclusions: Six cycles of chemotherapy reduced the risk of relapse within 2 years, but the benefit from two additional cycles beyond this time is questionable. Copyright © 2012 S. Karger AG, Basel.
Keywords: Chemotherapy; Early stage; Ovarian cancer; Paclitaxel